A naphthalimide-based fluorescent probe for quantitative sensing of UV light. (October 2022) - Wang, Maolin; Wei, Tingwen; Jiang, Long; Wang, Jing; Li, Yajing; Wu, Wenyan; Huang, Xiaojian; Wang, Fang; Lu, Sheng; Chen, Xiaoqiang
Abstract: Developing ultraviolet (UV) sensors that can visualize UV light in the environment for productive life has been widely practiced. A challenging problem that arises in this domain is the quantitative analysis of UV light. In this study, we identified a novel naphthalimide derivative, NDGF, which can undergo decomposition to various degrees when irradiated by UV light with different intensities, so as to produce corresponding fluorescence intensities. Moreover, NDGF was prepared as a UV-responsive film NDGF-PEO which also has outstanding competence in the quantification of UV intensity. The surprising thing is that this novel UV-responsive decomposition mechanism of NDGF has been demonstrated and has great potential to open new doors for the development of naphthalimide-based photocages and novel UV quantitative sensors. Graphical abstract: An innovative photocage-type UV sensor was developed for quantifying UV intensity and responding to the UV intensity of sunlight. Image 1 Highlights: A photocage-type probe NDGF for the detection of UV intensity was prepared. The novel photolyzed sensing mechanism of NDGF was proved. NDGF-PEO can reliably quantify UV intensity as a portable fiber film sensor. NDGF-PEO can respond well to solar UV intensity during one day.